Penyuluhan Hukum Sehubungan dengan Pembuatan Akta oleh Notaris sebagai Pejabat Umum - Eka Prasetya Rini; Diana Haiti (Lembaga Yasin AlSys, 2026)
Although the authority of notaries to provide legal counseling has been regulated in Article 15 paragraph (2) letter e of the Notary Office Law (UUJN), normative ambiguity regarding the definition, scope, and limits of this authority still gives rise to multiple interpretations and differences in practice. This study aims to analyze the ratio legis of this provision and its relevance to the social function of notaries as public officials. This study uses a normative legal method that is descriptive-analytical and prescriptive in nature, with statutory, conceptual, and historical approaches. Primary legal materials include the UUJN, the Advocate Law, and the Notary Code of Ethics, while secondary legal materials comprise relevant legal literature and scholarly journals. The results of the study show that the ratio legis of the authority of notaries to provide legal counseling is built upon three interrelated main pillars, namely philosophical, sociological, and juridical reasons. Philosophically, this authority reflects the implementation of the Pancasila rule-of-law state, preventive justice, and the principle of officium nobile. Sociologically, this authority is relevant to the low level of public legal awareness and limited access to advocate services. Juridically, legal counseling by notaries needs to be understood as an authority that is aligned with the main function of notaries and does not conflict with the regulation of the advocate profession. The conclusion of the study affirms that the authority to provide legal counseling is a manifestation of the social function of notaries as public officials, but the normative ambiguity in its regulation requires the formulation of clearer operational definitions and limits of authority. The implications of this study provide theoretical contributions to the development of notarial law as well as practical recommendations for the formulation of implementing regulations to ensure legal certainty for notaries and the public.